Trade and Race-to-the-bottom Wage Competition - Damiaan Persyn (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2006)
This paper looks at how increasing economic integration affects wage bargaining between unions and firms if firms are internationally mobile. Using a simple NEG model we find that if firms are perfectly mobile, countries are sufficiently symmetric and wages are bargained over at the firm level they are set on the competitive level. For a more centralised bargaining scheme wage demands are made even if firms can perfectly threat to relocate. If countries are asymmetric full agglomeration becomes possible and rent-sharing between unions and firms then occurs as unions are able to appropriate part of the agglomeration rents in firm of higher wages. As agglomeration rents are a hump-shaped function of trade freeness in the larger country this implies the same non-monotonic relationship between wages and the level of trade freeness. We then investigate the case where wage bargaining takes place sequentially in each country. The comparative statics of the international Nash-equilibrium in wages show increased international economic integration only leads to tighter international wage competition if countries are sufficiently symmetric. For the asymmetric case the comparative advantage and relative size of the country detfirmine whether and how economic integration leads to lower wages.
Keywords: J50; J31; F16; 330; Lohnverhandlungen; Multinationales Unternehmen; Internationaler Wettbewerb; Lohnbildung; Lohntheorie